Transformasi Pelayanan Masyarakat melalui Website Kampung Malasigit sebagai Inovasi Berbasis TI - Rumetna, Matheus Supriyanto; Hetharia, Charliany (Jurnal Teknologi Terpadu, 2024)
Malasigit Village is improving in terms of development and community services. The dissemination of information is still a significant problem; the information provided sometimes needs to reach the community. For example, health services related to the village community still need to be more efficient because sometimes the information provided by the assistant health center regarding health checks does not reach the village community. Another problem is related to the community's agricultural products; the condition that occurs is that agricultural products must be taken to be sold to the city, which is ± 30 km away and the understanding of village officials in the IT field, namely the use of computer devices and their applications. For this reason, village development is needed through IT, in this case, a website-based village information system to help village officials deliver transparent and efficient village information, providing service facilities/containers for farmers to promote their agricultural products to improve community services. This study uses the Waterfall method, website modelling using case diagrams and activity diagrams, which produce a home menu, profile, structure, facilities, news, information, gallery and contact.